AB0702 Entheses Scores in Clinical Practice – Correlation with Parameters of Disease Activity. (10th June 2014) - Abelha-Aleixo, J.; Madureira, P.; Vieira, R.; Fonseca, R.; Gonçalves, D.; Bernardes, M.; Bernardo, A.; Costa, L.
Abstract : Background: Enthesitis is a common and well described condition in spondylarthropathies. Currently several scores attempt to cover all affected areas in a practical way so that allows a reproducible assessment. Objectives: To evaluate whether there is a correlation between the scores of entheses (SPARCC and MASES) and several clinical and laboratory parameters in patients with ankylosing spondylitis (AS) and psoriatic arthritis (PsA). Methods: We made a retrospective analysis (July/2012 and December/2013) of all patients with AS and PsA under TNF antagonists treatment, using the national database for rheumatic patients. The demographic, clinic and laboratorial data, disease activity scores (ASDAS, BASDAI and DAS28-4V), quality and functional impairment parameters (HAQ, BASMI and BASFI), pain scales (EVAs) and entheses scores were collected. The Spearman correlation test was used (SPSS 21.0 for statistical data analysis). Results: We analysed 114 patients with ankylosing spondylitis (65, 8% men) with a median age of 45, 0 years [19, 1-79.9]; and 44 patients with psoriatic arthritis, (59, 1% women) with a median age of 48, 2 years [21, 1-85, 3]. The median disease duration was 21, 6 years [2, 5-49, 5]) and 13, 3 years [2, 5-40, 5], respectively. In the AS patients, moderate correlation (p<0.05) was found between both SPARCC and MASES and: ASDAS (r=0, 35: r=0, 31), BASDAI (r=0, 50; r=0, 54), BASFI (r=0, 30; r=0, 33), global disease pain patient evaluation (r=0.34; r=0.33), global disease pain doctor evaluation (r=0, 43; r=0, 32), spine night pain evaluation (r=0, 46; r=0, 37), and spine global pain evaluation (r=0, 38, r=0, 39). In the PsA patients, moderate to strong correlations (p<0.05) were found between both SPARCC and MASES and ASDAS (r=0, 63; r=0, 54), BASDAI (r=0, 68; r=0, 53), BASFI (r=0, 52; r=0, 41), DAS28 (4V) (r=0, 72; r=0, 47), HAQ (r=0, 68; r=0, 49) global disease pain patient evaluation (r=0.66; r=0.51), spine night pain evaluation (r=0, 55; r=0, 38), and spine global pain evaluation (r=0, 54; r=0, 38). Additionally SPARCC showed correlation with BASMI (r=0, 39) and global disease pain doctor evaluation (r=0, 59). No correlation was found between the scores of entheses and laboratory parameters (ESR and CRP), in both diseases. Conclusions: This analysis suggests there is a correlation between the enthesis scores and the majority of the parameters evaluated, for AS and PSA patients. We may infer the usefulness of entheses scores as an evaluation tool, but more studies are needed to assess its prognostic power. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5711